IMPLEMENTASI KEBIJAKAN PROGRAM PARKIR BERLANGGANAN DALAM MENUNJANG PENDAPATAN ASLI DAERAH (PAD) KABUPATEN SAMPANG - Try Ferisiansyah; Suci Megawati (Universitas Negeri Surabaya, 2022)
The development of an area is followed by an increase in population mobility and traffic growth in terms of the number of vehicles that are increasing, causing a shortage of parking areas with an imbalance between parking supply and demand. To find a solution for how the parking system can operate more efficiently by implementing a subscription parking fee that can simultaneously support Regional Original Income (PAD). This research was made to know and describe the quality of subscription parking services in Sampang Regency and to find out and describe the implementation of the subscription parking policy in supporting local revenue. The main issue that develops in it leads to the low quality of service provided by government officials. This research uses qualitative methods with descriptive types. The focus of this research is (1) The implementation of subscription parking services in Sampang Regency has been able to support Regional Original Revenue or not, (2) Constraint factors in subscription parking services in Sampang Regency, and (3) Efforts that must be made by the Transportation Service to improve the quality of parking services subscribe to subscribed parking service users. The results of this study indicate that the subscription parking policy has not been able to support Regional Original Revenue (PAD), and in the implementation of subscription parking services in the Sampang Regency, it still needs to be improved.